POST-REPORTING EVENTS DISCLOSURE UNDER PSAK 210: EVIDENCE FROM PT UNITED TRACTORS TBK AND ITS IMPLICATIONS FOR FINANCIAL REPORTING QUALITY - Athaya Allifia; Aufi Sekar Galih; Amanda Wulandari; Rimi Gusliana Mais (Universitas Tulungagung, 2025)
The convergence of Indonesian Financial Accounting Standards with International Financial Reporting Standards has strengthened the importance of transparent disclosure of events occurring after the reporting period through PSAK 210. Despite this regulatory development, empirical evidence regarding the implementation of PSAK 210 remains limited, particularly in industries characterized by complex strategic investments. This study aims to analyze the implementation of PSAK 210 by PT United Tractors Tbk, evaluate its compliance with post-reporting event disclosure requirements, and identify opportunities for improving disclosure quality. A qualitative approach employing content analysis was adopted. The study utilized secondary data comprising the 2023 Annual Report, 2023 Consolidated Financial Statements, Notes to the Financial Statements, Independent Auditor's Report, and other official corporate publications of PT United Tractors Tbk. Data were analyzed through documentary analysis to evaluate the classification and disclosure of events after the reporting period in accordance with PSAK 210. The findings indicate that the company appropriately classified the additional investment in PT Supreme Energy Sriwijaya as a non-adjusting event because the legal recognition criteria had not been fulfilled at the reporting date. The transaction was therefore disclosed in the Notes to the Financial Statements and subsequently recognized in the 2024 financial statements after legal ownership was established. Although the company substantially complied with PSAK 210, disclosure quality could be further improved through explicit reference to the standard and the inclusion of quantitative information regarding the expected financial impact of material post-reporting events. This study contributes to the literature on PSAK 210 implementation and provides practical guidance for enhancing transparency, accountability, and financial reporting quality among publicly listed companies in Indonesia.